Relationship of Work Tasks Motivation, Teaching self-efficacy and Teaching Emotions with Psychological Well-being in Teachers - Faezeh Khatami; Hossein Jenaabadi; Afsaneh Marziyeh (Iranian Journal of Educational Research)
Objective: The objective of this study was to conduct an investigation into the correlation between work tasks motivation, self-efficacy in teaching, and teaching emotions to psychological well-being in teachers. Methods: The research methodology employed in this study was descriptive in nature, utilizing correlation analysis. The statistical population for this research consisted of both male and female teachers from the first level of secondary schools in Birjand city (Iran) in 2023, totaling 612 individuals (379 female teachers and 233 male teachers). From this population, a random sample of 235 teachers was selected in accordance with the Morgan table. The research instruments utilized in this study were the Psychological well-being questionnaire (Reif, 1980), Teacher self-efficacy questionnaire (Tschannen-Moran et al., 2001), The Work Tasks Motivation Scale for Teachers (WTMST) (Ferrant et al., 2008), and Questionnaire in Emotionality in Teaching (Villavicencio, 2010). Pearson's correlation coefficient was employed to test the research hypotheses. Results: The findings of this study revealed a significant correlation between motivation in work tasks, self-efficacy in teaching, teaching emotions, and the psychological well-being of teachers (P<0.01). Conclusion: It can be concluded that motivational factors have the potential to enhance the psychological well-being of teachers, subsequently leading to improved teaching quality and effective classroom management.